2012
DOI: 10.1145/2071368.2071372
|View full text |Cite
|
Sign up to set email alerts
|

Succinctness of the Complement and Intersection of Regular Expressions

Abstract: Abstract. We study the succinctness of the complement and intersection of regular expressions. In particular, we show that when constructing a regular expression defining the complement of a given regular expression, a double exponential size increase cannot be avoided. Similarly, when constructing a regular expression defining the intersection of a fixed and an arbitrary number of regular expressions, an exponential and double exponential size increase, respectively, can in worst-case not be avoided. All ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 45 publications
1
46
0
Order By: Relevance
“…Again, Lemma 3.5 becomes pspace-complete. Since the smallest expression for the intersection of two regular expressions can be exponential, and since complementing a regular expression can cause a double-exponential blow-up [11], we have an (optimal) exponential upper bound for Theorem 3.7 and an optimal double exponential upper bound for Theorem 3.10. For deterministic regular expression the complexity of all decision problems remains the same as there is an efficient translation to DFAs.…”
Section: Content Modelsmentioning
confidence: 99%
“…Again, Lemma 3.5 becomes pspace-complete. Since the smallest expression for the intersection of two regular expressions can be exponential, and since complementing a regular expression can cause a double-exponential blow-up [11], we have an (optimal) exponential upper bound for Theorem 3.7 and an optimal double exponential upper bound for Theorem 3.10. For deterministic regular expression the complexity of all decision problems remains the same as there is an efficient translation to DFAs.…”
Section: Content Modelsmentioning
confidence: 99%
“…Also the classes RE(#) [22,27] and RE(&) [12,24] have received interest. Succinctness of regular expressions has been studied by Ehrenfeucht and Zeiger [8] and, more recently, by Ellul et al [9], Gelade and Neven [13], Gruber and Holzer [15][16][17][18], and Gruber and Johannsen [19]. See the Ph.D. theses of Gruber [14] and Gelade [11] for an overview of many of the recently obtained results.…”
Section: Re(#)mentioning
confidence: 99%
“…For RE(#) and RE(∩) the complexity of this translation has already been settled and is exponential [22] and double exponential [13], respectively. We show that also in constructing an expression for the interleaving of a set of expressions (an hence also for an RE(&)) a double exponential size increase cannot be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Brüggemann-Klein and Wood showed that it is decidable whether a given regular language is definable by a DRE. Since then, DREs have been studied in the context of language approximations [3], learning [4], descriptional complexity [13,21] and static analysis [8,9]. Recently, it was shown that testing if a regular expression is deterministic can be done in linear time [14].…”
Section: Introductionmentioning
confidence: 99%